2013
DOI: 10.1088/0031-9155/58/17/5833
|View full text |Cite
|
Sign up to set email alerts
|

Real-time temperature estimation and monitoring of HIFU ablation through a combined modeling and passive acoustic mapping approach

Abstract: Passive acoustic mapping (PAM) has been recently demonstrated as a method of monitoring focused ultrasound therapy by reconstructing the emissions created by inertially cavitating bubbles (Jensen et al 2012 Radiology 262 252-61). The published method sums energy emitted by cavitation from the focal region within the tissue and uses a threshold to determine when sufficient energy has been delivered for ablation. The present work builds on this approach to provide a high-intensity focused ultrasound (HIFU) treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…However, the information obtained from a single-element PCD is fundamentally limited due to the inherent trade-off between the volume of sensitivity and spatial specificity of the device. The use of multielement arrays, combined with passive beamforming algorithms borrowed from other fields, [45][46][47][48] has been shown to overcome this limitation and enable spatial mapping of cavitation activity during the application of FUS in both in vitro [49][50][51][52][53][54][55][56][57][58][59][60][61][62] and in vivo [63][64][65][66][67] settings. The integration of passive imaging during mechanicalbased FUS brain therapies would make the procedures practical, by providing a method for real-time treatment monitoring and control.…”
Section: Introductionmentioning
confidence: 99%
“…However, the information obtained from a single-element PCD is fundamentally limited due to the inherent trade-off between the volume of sensitivity and spatial specificity of the device. The use of multielement arrays, combined with passive beamforming algorithms borrowed from other fields, [45][46][47][48] has been shown to overcome this limitation and enable spatial mapping of cavitation activity during the application of FUS in both in vitro [49][50][51][52][53][54][55][56][57][58][59][60][61][62] and in vivo [63][64][65][66][67] settings. The integration of passive imaging during mechanicalbased FUS brain therapies would make the procedures practical, by providing a method for real-time treatment monitoring and control.…”
Section: Introductionmentioning
confidence: 99%
“…Such a system has many possible uses in clinical applications. Figure 2.58 shows localization of several cavitation sources by the PCI algorithm (Jensen et al 2013). Because passive beamformed map of original data shown in Fig.…”
Section: Time-domain Pcmmentioning
confidence: 99%
“…By using a digital comb filter with a bandwidth of 300 kHz for each comb, each channel was filtered in the frequency domain to obtain the broadband signal and the harmonics of the 1.06-MHz HIFU signal corresponding to inertial and stable cavitation, respectively (Gyöngy 2010). Jensen et al (2013) used a linear array (5-10 MHz) which is placed coaxially with 1.06-MHz HIFU transducer to passively receive emissions from bubbles in the ex vivo ox liver samples. As shown in Fig.…”
Section: Time-domain Pcimentioning
confidence: 99%
“…Moreover, when the amplitude of HIFU increased, such that the lesion region became overexposed and the tissue boiled, Jensen showed that both the broadband and harmonic maps shifted toward the HIFU transducer, which indicates a prefocal movement of cavitation activity (Bailey et al 2001). Jensen et al (2013) deemed that this experiment, in which the signals were processed straightly in the time domain, verified the effectiveness of the PCI method in tissue, whereby it nondestructively showed the location of the HIFU focus and gave a quantitative prediction of the lesion occurrence during HIFU treatment. The distribution of HIFU lesion region can be calculated by cumulative intensity of acoustic emissions from cavitation bubble; therefore, PCI can be used to dynamically predict HIFU focus and determine the damage position.…”
Section: Time-domain Pcimentioning
confidence: 99%